Exploring marine ecosystems with elementary school Portuguese children: inquiry-based project activities focused on ‘real-life’ contexts - Guilherme, Elsa (2021)
The purpose of the study was to investigate how young students engage in an inquirybased project driven by real-life contexts. Elementary school children were engaged in a small inquiry project centred on marine biodiversity and species adaptations. All activities included the exploration of an out-of-school setting as a learning context. A total of 49 students and 2 teachers were involved in the activities. The research methods included observation, document analysis and content analysis of the answers to a questionnaire and an interview. The results revealed that most of the students acquired scientific knowledge related to biological diversity and adaptations to habitat. Moreover, students progressively demonstrate greater autonomy, argumentative ability and decision-making. One implication of the present study is that elementary science curriculum could be better managed with inquiry projectbased activities that explore different types of resources and out-of-school settings.